The framework and features of language policies in global constitutional texts - Zhang, Chen; Zhao, Ronghui; Huang, Yan (Frontiers in Psychology, 2023)
Language policy, which is directly concerned with language practice, language ideology and language management, has become increasingly important in real social life. Explicit language policies in different fields, such as texts in law, education, and the public, have been explored for many years. However, the global comparative research on language policies in various constitutional texts (CT) is quite limited. In response, based on the large-scale data from constituteproject.org, the present study aimed 1) to generalize a framework of language policy based on constitutional provisions, 2) to analyze the relationship between the frequency of language policies and the parts of framework in which they were distributed, 3) and to explore the effect of geographic location on the frequency distribution of language policies. Results showed that: 1) there were seven parts of the CT dealing with language policies, such as Preamble, General principle, The state, Fundamental rights and Duties of citizen, State authority, National objectives, and Supplementary; 2) there existed significant differences in the frequency of language policies in seven parts of the CT. Among them, language policies appeared most frequently in the part of Fundamental rights and duties of citizen; 3) the geographical location where the Constitution was enacted affected the distribution of language policies across parts. Overall, based on both qualitative and quantitative analyses, our findings suggested that the language policy in CT was influenced not only by constitutional principles, but also by the national language environment.